Niet Ontvankelijke Verklaard (Di NO) Case of Annulment of Marriage Due to an Arranged Marriage - Sari, Anggun Purnama; Setiyawan, Deni (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze the decision of Niet Ontvankelijke Verklaard (NO) or the inadmissibility of the case in the case of marriage annulment based on an arranged marriage agreed by the parties, as well as to examine the legal basis, the judge's considerations, and the legal implications for the protection of the rights of the parties harmed in the marriage. The phenomenon of arranged marriages still often occurs in society for reasons of custom, economics, or family honor. However, when the marriage is filed for annulment to the religious court, it is not uncommon for the application to be declared Niet Ontvankelijke Verklaard because it is considered not to meet the formal and material requirements according to the provisions of civil procedural law and Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. This study uses a normative juridical method with a case approach and a statute approach, through an analysis of court decisions that declare the case inadmissible. The results of the study indicate that the main reasons for the judge to issue an NO decision are the failure to fulfill the legal standing requirements, the incompleteness of the object of the lawsuit, and formal defects in the petition for annulment. Furthermore, the agreement to an arranged marriage by the parties to the marriage is considered voluntary, thus failing to meet the element of coercion that constitutes the basis for annulment. The NO ruling has the legal implication that the case was not examined to its core, allowing the parties to resubmit the lawsuit with formal amendments. In conclusion, the Niet Ontvankelijke Verklaard ruling in the case of annulment of a marriage based on an arranged marriage does not mean the marriage is fully valid, but rather indicates an inaccuracy in the lawsuit filing procedure that must be improved to achieve legal certainty and protect individual rights in marriage.